KAPASITAS PELAT LANTAI METODE HALF-SLAB DAN METODE KONVENSIONAL BERDASARKAN VARIASI KETEBALAN - Tri Handayani; Aprilin, Ririt; Murtinugraha, R. Eka (Jurnal Pendidikan Teknik dan Vokasional, 2020)
Innovation in floor plate methods has been developing nowadays, one of the methods is the precast method. However, this method cannot behave monolithically with other structures so that the deflection does not meet the permit. To overcome this problem then the half-slab plate innovation comes with a combination of precast and conventional method for the topping. This study discusses the ratio of half-slab and conventional floor plate capacity based on the thickness variation. The capacity analysis covers the bending moment, shear force, deflection and stress due to gravity loads. The total thickness of plate was 120 mm and 130 mm, with the three thickness variations which were the precast is thicker than the topping, the topping is thicker than the precast, and the topping is equal to the precast. The results show that the half-slab plate capacity is 8 to 20 times larger than the conventional plate, due to the lifting and shoring forces. In addition, the variations in the topping and precast thickness affect the value of half-slab capacity, which is the thicker the precast the greater the capacity. Adding thickness every 5 mm could increase the moment capacity by 1,58-7,14%, the shear capacity by 1,61-7,14%, the deflection by 1,69-2,08% and could decrease the normal voltage by 1,76%. So the good variation in the half-slab plate thickness is the plate with the precast thickness which is smaller than the topping thickness. From the two types of plates, plates with a thickness of 130 mm have the capacity 4 to 8 times larger than 120 mm. This is influenced by the lift point placement, shoring plots and a larger 130 mm plate width. Keywords: floor plate capacity, half-slab, thickness variation